2022
DOI: 10.3389/fphys.2022.847895
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antennal Chemosensilla and Associated Chemosensory Genes in the Orange Spiny Whitefly, Aleurocanthus spiniferus (Quaintanca)

Abstract: The insect chemosensory system plays an important role in many aspects of insects’ behaviors necessary for their survival. Despite the complexity of this system, an increasing number of studies have begun to understand its structure and function in different insect species. Nonetheless, the chemosensory system in the orange spiny whitefly Aleurocanthus spiniferus, as one of the most destructive insect pests of citrus in tropical Asia, has not been investigated yet. In this study, the sensillum types, morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs), which are involved in the binding and transport of odor molecules, are also expressed in tissues outside the antennae (Yi et al 2015;Lizana et al 2022). Tissue-speci c transcriptome analysis revealed that CSPs are widely expressed in both the head (including the antennae) and body tissues of adult orange spiny white ies (Gao et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs), which are involved in the binding and transport of odor molecules, are also expressed in tissues outside the antennae (Yi et al 2015;Lizana et al 2022). Tissue-speci c transcriptome analysis revealed that CSPs are widely expressed in both the head (including the antennae) and body tissues of adult orange spiny white ies (Gao et al 2022).…”
Section: Discussionmentioning
confidence: 99%